If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-14+18=-2(x+7)
We move all terms to the left:
-14+18-(-2(x+7))=0
We add all the numbers together, and all the variables
-(-2(x+7))+4=0
We calculate terms in parentheses: -(-2(x+7)), so:We get rid of parentheses
-2(x+7)
We multiply parentheses
-2x-14
Back to the equation:
-(-2x-14)
2x+14+4=0
We add all the numbers together, and all the variables
2x+18=0
We move all terms containing x to the left, all other terms to the right
2x=-18
x=-18/2
x=-9
| -15+3x=3(x-15) | | 6(x+7)-8x=28 | | (d/12)+780+(d/8)=1080 | | 3x-5÷3x=x+8-x-1 | | 2x+6=6(x+3) | | 3(0.5x-4=3/2x-1.2 | | w-4/2=2 | | 28=7+3x^2 | | 4(y+2)=2(3+1) | | F(1998x)=2.4x+54.4 | | 25x+60=375 | | 2(x-3)-7=23 | | -3x+17=10 | | 12x+17=14x+-1 | | 8(7-3k)-8=2-k | | 20c+4c-20c=4 | | 17x-11+17=180 | | 3n-3-4n=1 | | d/12+780+d/8=1080 | | 8u+u-7u-1=15 | | -6+3|2x+3|=0 | | 4z-4z+z=18 | | 8x-1+x=179 | | 15=c/2-3 | | -9+x+2x+3=3(x+2) | | F(x)=2.4x+54.4 | | 8x+48=3x+99 | | 9=(y÷-3)-6 | | (h-5)/14=(h-3)/(2h+3) | | -5d+4=29 | | -x+10=218 | | 24=6y-6 |